STUDI PERBANDINGAN KEBIJAKAN INDUSTRI 4.0 INDONESIA DENGAN TIGA NEGARA LEADING GROUP FUTURE OF PRODUCTION - Hari Wisnu Murti (Kementerian Perindustrian); M. Tirtana Siregar (Politeknik APP Jakarta, 2021)
AbstractThe World Economic Forum has compiled a profile of future of production readiness among 100 countries in the world where Indonesia is in the nascent group and requires benchmarking to the leading groups through SWOT Analysis. This study aims to compare Indonesia's industry 4,0 policy with leading countries through a comparative study. The data is obtained from industry 4.0 policy from Indonesia and three leading countries. The results of the study indicate that the Making Indonesia 4.0 policy is on the right track to pursue manufacturing competence and answer future challenges that will be faced by Indonesia and the current baseline, has weaknesses in priority sectors that do not support increased complexity. Opportunities that can be taken are trade infrastructure with other countries, investment opportunities for countries that lack human resources, and cooperation in sustainability standards. The challenge lies in the common priority sectors of the industry and the absence of AI research priorities for health and biotechnology while Indonesia has a large domestic market.AbstrakWorld Economic Forum menyusun profil kesiapan industri masa depan pada 100 negara di dunia dimana Indonesia tergolong kelompok Nascent dan membutuhkan pembandingan dengan negara-negara kelompok Leading melalui analisa SWOT, Studi ini bertujuan untuk membandingkan kebijakan industri 4.0 Indonesia dengan negara-negara kelompok Leading melalui studi komparatif. Data diperoleh dari kebijakan industri 4.0 dari Indonesia dan tiga negara kelompok leading. Hasil dari studi mengindikasikan bahwa kebijakan Making Indonesia 4.0 telah pada jalur yang tepat untuk mengejar kompetensi manufaktur dan menjawab tantangan masa depan yang akan dihadapi Indonesia dan baseline saat ini, mempunyai kelemahan pada sektor prioritas yang tidak mendukung peningkatan kompleksitas. Peluang yang bisa diambil adalah infrastruktur perdagangan dengan negara lain, peluang investasi untuk negara yang kurang dalam sumber daya manusia, dan kerjasama standar sustainability. Tantangan ada pada kesamaan sektor prioritas industri dan belum adanya prioritas riset AI untuk kesehatan dan bioteknologi sementara Indonesia mempunyai pasar domestik yang besar.